Intangible and tangible value: brand equity benefits associated with collegiate athletics. Issue 4 (1st July 2015) - Bozman, Carl S; Friesner, Daniel; McPherson, Matthew Q; Chase, Nancy M
Abstract : This paper presents a simple methodological framework to characterise the tangible and intangible benefits of a university athletics department. The methodology is applied to the athletics department at Gonzaga University (GU) in Spokane, Washington USA. The brand equity associated with this department is estimated at approximately US5.8 million in 2006. Of this, between 617, 000 and 2.71 million is ascribed to a specific type of tangible brand equity (with the most plausible estimate being 926, 000); namely, the impact of GU athletics events on the economic vitality of the local community. The remainder is attributed to (unobserved) intangible brand equity benefits.